The Duke, the Soldier of Fortune, and a Rosicrucian Legacy: Exploring the Roles of Manuscripts in Early-Modern Alchemy. (3rd April 2018) - Zuber, Mike A.
Abstract : By the time it was published in 1705, the Speculum Sapientiae claimed to have had a long history going back to 1672. However, the fact that exaggerated stories were commonplace in alchemical literature leads us to question its credibility. This paper explores the secret lives of this alchemical text prior to its print publication to clarify the roles of manuscripts in early-modern alchemy. Specifically, I argue that there were three aspects that could distinguish manuscript from print: provenance, materiality, and exclusivity. These can be seen at work in the fate of Johann Heinrich Vierordt, an itinerant alchemist and cavalry captain whose career is inextricably linked to the scribal dissemination of the Speculum Sapientiae . In addition to manuscript copies of that text at libraries across Europe, a significant cache of correspondence preserved in Gotha documents Vierordt's dealings with Duke Friedrich I of Saxe-Gotha. The verisimilitudinous provenance of Vierordt's alchemical secrets and tincture played a crucial role in allowing him to gain Friedrich's trust. Yet it was only after Vierordt presented him with a precious parchment manuscript of the Speculum Sapientiae that he truly succeeded in gaining the duke's patronage. Subsequently, reports of multiple conflicting copies surfacing in Amsterdam sealed Vierordt's fall from favour.